P-NADs: PUX-based NAnobody degraders for ubiquitin-independent degradation of target proteins - Jun Wang; Georgy Chistov; Junrui Zhang; Brandon Huntington; Israa Salem; Anandsukeerthi Sandholu; Stefan T. Arold (Heliyon, 2024)
Targeted protein degradation (TPD) allows cells to maintain a functional proteome and to rapidly adapt to changing conditions. Methods that repurpose TPD for the deactivation of specific proteins have demonstrated significant potential in therapeutic and research applications. Most of these methods are based on proteolysis targeting chimaeras (PROTACs) which link the protein target to an E3 ubiquitin ligase, resulting in the ubiquitin-based degradation of the target protein. In this study, we introduce a method for ubiquitin-independent TPD based on nanobody-conjugated plant ubiquitin regulatory X domain-containing (PUX) adaptor proteins. We show that the PUX-based NAnobody Degraders (P-NADs) can unfold a target protein through the Arabidopsis and human orthologues of the CDC48 unfoldase without the need for ubiquitination or initiating motifs. We demonstrate that P-NAD plasmids can be transfected into a human cell line, where the produced P-NADs use the endogenous CDC48 machinery for ubiquitin-independent TPD of a 143 kDa multidomain protein. Thus, P-NADs pave the road for ubiquitin-independent therapeutic TPD approaches. In addition, the modular P-NAD design combined with in vitro and cellular assays provide a versatile platform for elucidating functional aspects of CDC48-based TPD in plants and animals.